Analysis of the Problem of Import Substitution in the Chemical Industry and its Impact on Other Sectors of the Economy - Yu. V. Kruglova (Управленческие науки, 2023)
In Russia, the issues of import substitution are now more acute than ever. In this article, these problems are examined in relation to various sectors of the economy, and first of all, to the chemical industry, which is the basis for technological progress and whose development makes it possible to create conditions for the emergence and implementation of innovations in other industries. The author of the study set out to analyze the situation with import substitution in the chemical industry, as well as related industries, using Rosstat data, existing research results on similar issues, and also based on her own experience. In the course of the work, the main trends in import substitution and existing opportunities for increasing it were identified. Scientific tools such as analysis, synthesis, statistical method and data visualization method were used as a methodological basis. The research results reflected in this article can be useful both to researchers of the development of high-tech industries, and to representatives of federal and regional executive authorities, and other interested parties.